2004
DOI: 10.1002/jpln.200220892
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of N2 fixation and annual N benefit from N2 fixation in soybean accrued to the soil under soybean‐wheat continuous rotation

Abstract: PNSS P89/2BSummary A computational exercise was undertaken to quantify the percent N derived from atmosphere %Ndfa) in soybean and consequent N benefit from biological N 2 -fixation process annually accrued to the soil by the soybean crop using average annual N-input/-output balance sheet from a 7 yr old soybean-wheat continuous rotational experiment on a Typic Haplustert. The experiment was conducted with 16 treatments comprised of combinations of four annual rates of farmyard manure (FYM @ 0, 4, 8, and 16 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The low N 2 fixation in UN 100 may be explained by the inhibitory effect of applied mineral N fertilizer on nodule formation and activity. In earlier studies, a significant reduction in N 2 fixation of soybean (lower than the control) was observed at each increased level of fertilizer N, as a result of which Ndfa values declined from 76% at N 0 to 27% at 230 kg N ha −1 (Singh et al, 2004). The possibility of substantial accumulation of NO 3 − –N in the soil under the N fertilizer treatment in this research severely suppressed nodulation, thereby decreasing N 2 fixation, consistent with many other studies (Peoples and Herridge, 1990).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The low N 2 fixation in UN 100 may be explained by the inhibitory effect of applied mineral N fertilizer on nodule formation and activity. In earlier studies, a significant reduction in N 2 fixation of soybean (lower than the control) was observed at each increased level of fertilizer N, as a result of which Ndfa values declined from 76% at N 0 to 27% at 230 kg N ha −1 (Singh et al, 2004). The possibility of substantial accumulation of NO 3 − –N in the soil under the N fertilizer treatment in this research severely suppressed nodulation, thereby decreasing N 2 fixation, consistent with many other studies (Peoples and Herridge, 1990).…”
Section: Resultsmentioning
confidence: 87%
“…The maximum amount of N 2 fixed was 43 kg N ha −1 at Hajira, while 73 kg N ha −1 was fixed at Rawalakot site the treatment supplemented with PM 100 . It has been recognized that a high level of organic matter buildup in soil due to the addition of organic amendments improves soil physical conditions and enhances nutrient levels and microbial activity that eventually increases N 2 fixation in soybean (Singh et al, 2004). The integrated use of UN with PM or WMR in our research improved N 2 fixation of soybean, suggesting that continuous use of organic amendments (PM and WMR) with mineral N had a beneficial effect on N 2 fixation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another major problem is that the root system is routinely not included in the BNF estimates, which may lead to soybean going from a net exporter (Di Ciocco et al 2011 ) to a net fi xer of soil N (Singh et al 2004 ). When considering the importance and number of agricultural systems in which soybean participates, this change may have signifi cant effects on overall N balance.…”
Section: Bnf Inputs To Agricultural Systemsmentioning
confidence: 96%
“…According to Sanginga et al (2010) this plant can fix annually 11-120 kg atmospheric nitrogen in the form of Nitrate. Further, Handarson et al (1989) reported that nitrogen fixation ability of the soybean crop is influenced by several factors such as plant varieties, soil types, climatic conditions, crop management practices, availability of organic matter (Kundu et al, 1996) and the availability of Phosphorus and Sulfur (Kris Joko, 2001;Singh, 2004).…”
Section: Introductionmentioning
confidence: 99%